2017
DOI: 10.1371/journal.pone.0187238
|View full text |Cite
|
Sign up to set email alerts
|

Emergency obstetric and newborn care signal functions in public and private facilities in Bangladesh

Abstract: BackgroundSignal functions for emergency obstetric and newborn care (EmONC) are the major interventions for averting maternal and neonatal mortalities. Readiness of the facilities is essential to provide all the basic and comprehensive signal functions for EmONC to ensure emergency services from the designated facilities. The study assessed population coverage and availability of EmONC services in public and private facilities in Bangladesh.MethodsAn assessment was conducted in all the public and private facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
4
13
1
Order By: Relevance
“…Therefore, there is a need to invest more on training and more investment on the safe blood transfusion services. The findings from this study is similar to that of Roy et al (2017) which was conducted in Bangladesh which showed that of all signal functions coverage for both Caesarean section and blood transfusion services had less than 1% [39].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, there is a need to invest more on training and more investment on the safe blood transfusion services. The findings from this study is similar to that of Roy et al (2017) which was conducted in Bangladesh which showed that of all signal functions coverage for both Caesarean section and blood transfusion services had less than 1% [39].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, there is a need to invest more on training and more investment on the safe blood transfusion services. The findings from this study is similar to that of Roy et al [38] which was conducted in Bangladesh which showed that of all signal functions coverage for both Caesarean section and blood transfusion services had less than 1%.…”
Section: Discussionsupporting
confidence: 89%
“…manual vacuum extraction, dilatation, and curettage), (vi) performing assisted vaginal delivery (AVD), i.e. vacuum extraction or forceps delivery, (vii) performing basic neonatal resuscitation), (viii) performing CS delivery, and (ix) Safe Blood Transfusion services to be available for 24 h a day, 7 days a week [36][37][38].…”
Section: Activity 4 Data Collection Procedures and Toolsmentioning
confidence: 99%
“…However, the role of village doctors as the predominant providers for the poor in this context cannot be ignored and our findings suggest they are already integrated in infection management practices for young infants in the community. Previous research has promoted public-private partnerships (PPP) to improve nationwide coverage of emergency obstetric and newborn care in Bangladesh [55]. Future studies are needed to examine the potential for engaging informal and formal private providers, including the potential for fostering public-private partnerships (PPP) in this context [18,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to examine the potential for engaging informal and formal private providers, including the potential for fostering public-private partnerships (PPP) in this context [18,53,54]. Previous research has promoted PPP to improve nationwide coverage of emergency obstetric and newborn care in Bangladesh [55]. Additionally, public sector providers' opinions around engaging with private providers as allies should be explored as this has previously been identified as a barrier to implementation of PPP [56].…”
Section: Discussionmentioning
confidence: 99%